PERAN NOTARIS DALAM PENCEGAHAN TINDAK PIDANA PENCUCIAN UANG DI ERA DIGITAL MELALUI APLIKASI GO ANTI MONEY LAUNDERING (GoAML) - Eliya Al-Afrida Siska; Supriyadi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Notaries’ roles in performing their functions and duties to prevent money laundering have been stipulated in Article 3 of Government Regulations No. 43 of 2015, which was a mandate from Article 2 paragraph (2) of the Criminal Act of Money Laundering Law. Notaries must report suspicion of money laundering to the Financial Transaction Reports and Analysis Center (PPATK). It is based on the ideal framework law to be achieved by a country, which must fulfill 3 (three) fundamental values, namely expediency, certainty, and justice. Notaries’ roles in serving the community must also be able to provide accountability for the civil law so it does not harm the country with an attempt to disguise money from money laundering.